Benign Paroxysmal Positional Vertigo: What We Do and Do Not Know - Nuti, Daniele; Zee, David S.; Mandalà, Marco (Seminars in Neurology, 2020)
Benign paroxysmal positional vertigo (BPPV) is common, sometimes terrifying, but rarely portends serious disease. It is usually easily diagnosed and treated, and both the patient and the physician are immediately gratified. While much has been learned about the pathogenesis of BPPV in the past decades, many of its features remain mysterious, and one must still be wary of the rare times it mimics a dangerous brain disorder. Here we review common, relatively well understood clinical features of BPPV but also emphasize what we do not know and when the physician must look deeper for a more ominous cause.
Keywords: positional vertigo; positional nystagmus; canalolithiasis; cupulolithiasis